Syngas biomethanation: In a transfer limited process, is CO inhibition an issue?. (1st May 2023) - Figueras, J.; Benbelkacem, H.; Dumas, C.; Buffiere, P.
Highlights: CO inhibition was investigated on a consortium adapted for syngas biomethanation. The experiments were performed in continuous mode on a pressurized stirred column. No inhibition was observed for an inlet CO partial pressure up to 5 bar. CO is consumed faster than it is transferred, keeping a low dissolved concentration. Abstract: Syngas biomethanation is a promising technology in the process chain converting wastes to methane. However, gas–liquid mass transfer is a limiting factor of the biomethanation process. To reach high methane productivity, increasing the pressure is an interesting strategy to improve mass transfer. However, the CO content in the syngas raises concerns about a potential inhibition of the microorganisms. Therefore, the aim of the research was to assess the ability to work at high CO partial pressures. In this regard, a pressurized continuous stirred column with a working volume of 10 L was implemented and a consortium adapted for syngas-biomethanation for 22 months was submitted to 100% CO and increasing pressure. No inhibition phenomenon was observed for logarithmic PCO as high as 1.8 bar (inlet pressure 5.0 bar), which was the first time that such a high CO partial pressure was tested in continuous mode. Mass transfer limitations allowed for the carboxydotrophic microorganisms to consume CO faster than it was transferred, allowing for the dissolved CO concentration to remain under inhibitory concentrations. These results question the habitual consensus that CO inhibition is a limiting factor of syngas biomethanation.